2002
DOI: 10.1034/j.1399-6576.2002.460605.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidural buprenorphine in management of pain in multiple rib fractures

Abstract: Epidurally introduced narcotic, like buprenorphine in saline, has been found to be effective in our study to achieve adequate analgesia in treatment of patients with multiple rib fractures. In addition, this methodology of pain relief eliminates the costly delivery system and early discharge, and allows walking epidurals and follow-up on outpatient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Overall, it appeared that pain reduced faster and in a similar pattern for participants in the experimental group compared with participants in the control group who, in turn, experienced ups and downs in their experience of pain reduction. Many studies have shown the effectiveness of analgesics given for pain control in patients with rib fractures [5,7,29]. In the present study, it appeared that the active cycle of breathing techniques (ACBT) reduced the level of pain.…”
Section: Acbt Controlmentioning
confidence: 69%
“…Overall, it appeared that pain reduced faster and in a similar pattern for participants in the experimental group compared with participants in the control group who, in turn, experienced ups and downs in their experience of pain reduction. Many studies have shown the effectiveness of analgesics given for pain control in patients with rib fractures [5,7,29]. In the present study, it appeared that the active cycle of breathing techniques (ACBT) reduced the level of pain.…”
Section: Acbt Controlmentioning
confidence: 69%
“…[1415] In all three groups, 100% patients had analgesia till two hours. 50% of patients had analgesia up to 6 hours in group I, 3 hours in group II and 17 hours in group III.…”
Section: Discussionmentioning
confidence: 99%
“…23 Addition of buprenorphine intrathecally or epidurally provides a good postoperative analgesia without prolonged motor block. 14,15 A study by Shaloo Ipe et al observed that 150mcg buprenorphine was not as effective as 300 mcg buprenorphine given epidurally where the duration of analgesia was highest, though the analgesic effect of buprenrphine given intrathecally was quite effective with 50% patients showing the effect for 6 hours. 16 Some investigators have demonstrated that by using buprenorphine alone epidurally, in doses of 1 to 4 mg, varying durations of pain relief ranging from 2.5 to 9 hours are observed.…”
Section: Discussionmentioning
confidence: 99%